Predictors of students’ mental health during the COVID-19 pandemic: the impact of coping strategies, sense of coherence, and social support - Torinomi, Charlotte; Lindenberg, Katajun; Möltner, Andreas; Herpertz, Sabine; Holm-Hadulla, Rainer M. (International journal of environmental research and public health, 2022)
Young people and women seem to suffer more from social restrictions due to the COVID-19 pandemic than do others. Findings from pre-pandemic surveys identified students as a specific risk group for developing anxiety and depressive symptoms. Recent studies have indicated that students especially denoted a decrease in mental health during the pandemic. In a sample of n = 1938 university students (67.6% female), we investigated protective factors that are associated with mental health (defined as the absence of any mental disorder) and more specifically, the absence of major depression during the pandemic despite social restrictions. Investigated protective factors were social support, sense of coherence and situational coping strategies.